KOMPYUTERDE ORAYLÍQ SHEK TEOREMASÍN ESAPLAWDÍ ISKE ASÍRÍW - Kasımov, M.; Nurmaxanov, K.E. (ILIM hám JÁMIYET, 2025)
The main objective of this paper is to solve the central limit theorem problems presented in the STATISTICA 10 package with the possibility of computer implementation.